Tetraphenylethylene-functionalized hexaphenylbenzene with unique conformation-driven selectivity for gas chromatographic separations. (3rd February 2020) - Yang, Yinhui; Qi, Meiling; Wang, Jinliang
Abstract : Tetraphenylethylene-functionalized hexaphenylbenzene composed of a neat aromatic hydrocarbon with unique conformation-driven selectivity for gas chromatographic separations. Abstract : Here we report a novel hexaphenylbenzene (HPB)-based material functionalized with six tetraphenylethylene units (BPT) with unique conformation-driven selectivity for gas chromatographic (GC) separations. It is composed of a neat aromatic hydrocarbon with a rigid propeller-like conformation. As a result, the BPT capillary column exhibited high column efficiency of 5340 plates per m and high-resolution capability for aromatic to aliphatic isomers with excellent intra-day and inter-day repeatability and between-column reproducibility. The results demonstrate the unique conformation-driven selectivity of the HPB-based stationary phase, which is rarely reported for chromatography. Moreover, its application in the determination of isomer impurities in commercial products proved its good potential for practical GC analysis. This work presents a new perspective for developing selective stationary phases by engineering their structures.